An unusual case of optic neuritis - Dögel, Daniela; Müller, Wolf C.; Deckert, Martina; Lenhard, Thorsten; Schmidt-Bacher, Annette; Storch-Hagenlocher, Brigitte; Biller, Armin; Wildemann, Brigitte (Journal of neurological sciences, 2011)
Optic neuritis is a frequent disease with well established tests and therapeutic strategies. However, possible differential diagnoses cover a broad spectrum. Therefore, clinical work-up can be challenging and routine testing and therapies may not be sufficient. In this case, a 26year old female is described who presented with clinical features of optic neuritis, yet failed to respond to common therapeutic strategies and lost vision on the affected eye. Diagnostic nerve transection was performed, histopathology suggested inflammation. As the second nerve became affected, immunosuppressive therapy with cyclophosphamide was started and stopped further deterioration. Although additional molecular work-up of the transected nerve revealed clonal rearrangement of the B-cell-receptor-locus IgH, overall histopathologic features and the absence of systemic disease suggested an aggressive inflammatory process rather than lymphoma. Additional B-cell depletion with rituximab prompted significant and sustained visual improvement. This case emphasizes the necessity to consider rare differential diagnoses of optic neuritis, when uncommon features arise during the course of disease. Aggressive immunosuppression might be required to achieve stable improvement of vision.